Pre-leukemic Cell Detection and Leukemic Transformation of a Normal Marrow Cell: A Mini review - Chhetri, Bibek Rana; Thapa, Rajat; Shrestha, Dipika; Paudel, Agrani; Adhikari, Sandesh; Gautam, Arjun (International Journal of Applied Sciences and Biotechnology, 2022)
The hematopoietic cells are multipotent primitive cells, which differentiate into either common myeloid and lymphoid progenitor. However, if there an abnormality in this process of differentiation, condition of leukemia arises, which is the 11th leading cause of cancer-related mortality worldwide in the year 2018. These abnormalities are brought about by array of mutations occurring at cellular level. According to the two-hit model hypothesis, key oncogenic events are classified into two classes: class I mutations and class II mutations. Class I mutations are those that causes activation of the receptor tyrosine kinase (RTK), FLT3, c-kit (KIT), and Ras signaling pathways thereby increasing proliferation rate of progenitor cells. Class II mutations include recurrent chromosomal abnormalities such as t(8; 21), inv(16), and t(15; 17), which result in fusion transcripts of RUNX1/ETO, CBF/MYH11, and PML/RAR, respectively that eventually impair hematopoietic differentiation. The factors associated with leukemia can be biological, chemical or socio-economical. The advancement in the researches on the topic have aided to the development of various technologies such as detection of DNMT3A and xenografts assays, in order to detect these mutations in pre-leukemic cells. This review aims to provide an introduction to the condition, its types and provide brief summary on genes and mutations responsible for the condition. The factors associated with leukemia and technologies involved in the detection of leukemia are also reviewed.